The Use of Chimeric Antigen Receptor T Cells in Patients With Non-Hodgkin Lymphoma - Lulla, Premal D. (Clin Adv Hematol Oncol, 2018)
Resistance to conventional lines of therapy develops in approximately 20% of all patients with lymphoma. These patients have a dismal prognosis, with an expected median survival of 6.3 months. In recent years, T-cell immunotherapy has demonstrated a remarkable capacity to induce complete and durable clinical responses in patients with chemotherapy-refractory lymphoma. A major contributor to the success of immunotherapy has been the advent of genetic engineering technologies that introduce a chimeric antigen receptor (CAR) into T cells to focus their killing activity on tumor cells. The adoptive transfer of autologous CAR T-cell products specific for the pan–B-cell antigen CD19 have now received approval from the US Food and Drug Administration (FDA) for the treatment of relapsed or chemotherapy-resistant B-cell non-Hodgkin lymphoma. This review is designed to showcase the clinical efficacy and unique toxicities of individually developed CAR T-cell products for the treatment of lymphomas and their evolution from the laboratory bench to commercialization.